Hollow-Core Fiber-Tip Interferometric High-Temperature Sensor Operating at 1100 °C with High Linearity - Zhe Zhang; Baijie Xu; Min Zhou; Weijia Bao; Xizhen Xu; Ying Wang; Jun He; Yiping Wang (Micromachines, 2021)
Over decades, fiber-optic temperature sensors based on conventional single-mode fibers (SMF) have been demonstrated with either high linearity and stability in a limited temperature region or poor linearity and thermal hysteresis in a high-temperature measurement range. For high-temperature measurements, isothermal annealing is typically necessary for the fiber-optic sensors, aiming at releasing the residual stress, eliminating the thermal hysteresis and, thus, improving the high-temperature measurement linearity and stability. In this article, an annealing-free fiber-optic high-temperature (1100 °C) sensor based on a diaphragm-free hollow-core fiber (HCF) Fabry-Perot interferometer (FPI) is proposed and experimentally demonstrated. The proposed sensor exhibits an excellent thermal stability and linearity (R2 > 0.99 in a 100–1100 °C range) without the need for high-temperature annealing. The proposed sensor is extremely simple in preparation, and the annealing-free property can reduce the cost of sensor production significantly, which is promising in mass production and industry applications.